Comparison between electrospun and Bubbfil-spun Polyether sulfone fibers - Ya,Li (2014)
Electrospinning is a simple method for producing ultrafine fibers, and has attracted much recent interest. The classical approach was either polymer solutions or polymer melts. Bubbfil spinning (e.g. bubble-electrospinning) is a facile method to fabricate nanofibers with high surface area to volume ratio and high porosity. Polyether sulfone (PES) dissolved in N,N-Dimethylacetamide (DMAC) was used in this study to compare fiber morphologies of two technologies at the same spinning conditions. Effects of solution concentration, applied voltage and tip-to-collector distance on the morphology of the fibers were experimentally studied. It revealed that the Bubbfil spinning process is a better candidate for mass-production of nanofiber with controllable morphology.